2013
DOI: 10.1016/j.rbmo.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

GnRH agonist triggering: recent developments

Abstract: The concept that a bolus of gonadotrophin-releasing hormone agonist (GnRHa) can replace human chorionic gonadotrophin(HCG) as a trigger of final oocyte maturation was introduced several years ago. Recent developments in the area strengthen this premise. GnRHa trigger offers important advantages, including virtually complete prevention of ovarian hyperstimulation syndrome(OHSS), the introduction of a surge of FSH in addition to the LH surge and finally the possibility to individualize luteal-phase supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
66
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 35 publications
0
66
0
7
Order By: Relevance
“…Liu et al demonstrated that day 3 LH/FSH ≥ 2 is associated with higher rates of cancellation of IVF cycles since there was less expecting the number of Oocytes retrieved together with very poor maturation [5]. The hypothesis in conducting the present study was to observe whether elevated day 3 LH/FSH ratio ≥ 1 and above in high response women are really impacting IVF outcome (total number of oocytes retrieved and Total matured oocytes) while using different triggering medicine for ovulation stimulation [6] (Figures 1 and 2). …”
Section: Introductionmentioning
confidence: 84%
“…Liu et al demonstrated that day 3 LH/FSH ≥ 2 is associated with higher rates of cancellation of IVF cycles since there was less expecting the number of Oocytes retrieved together with very poor maturation [5]. The hypothesis in conducting the present study was to observe whether elevated day 3 LH/FSH ratio ≥ 1 and above in high response women are really impacting IVF outcome (total number of oocytes retrieved and Total matured oocytes) while using different triggering medicine for ovulation stimulation [6] (Figures 1 and 2). …”
Section: Introductionmentioning
confidence: 84%
“…Thus, many studies have focused on avoiding this iatrogenic complication using various strategies (2). It is well established that this syndrome almost always requires the exogenous administration of human chorionic gonadotropin (hCG) or endogenous pregnancy-derived hCG stimulation (3). However, due to its luteinizing hormone (LH) homology, extended half-life, and simple manufacturing process, hCG is an excellent trigger for final oocyte maturation (3).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that this syndrome almost always requires the exogenous administration of human chorionic gonadotropin (hCG) or endogenous pregnancy-derived hCG stimulation (3). However, due to its luteinizing hormone (LH) homology, extended half-life, and simple manufacturing process, hCG is an excellent trigger for final oocyte maturation (3). Nevertheless, the introduction of gonadotropin-releasing hormone (GnRH) antagonist protocols has allowed the utilization of a GnRH agonist (a) to induce final oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La administración de un análogo de GnRH induce una rápida liberación de LH y FSH, alcanzando niveles plasmáticos similares a los fisiológicos en el momento de la ovulación (5)(6)(7)(8). Sin embargo, son muchos los centros que no lo usan por temor a que sea menos eficiente en el proceso de inducir la maduración final de los ovocitos.…”
Section: Introductionunclassified